2006
DOI: 10.1021/bi061321b
|View full text |Cite
|
Sign up to set email alerts
|

The Androgen Receptor T877A Mutant Recruits LXXLL and FXXLF Peptides Differently than Wild-Type Androgen Receptor in a Time-Resolved Fluorescence Resonance Energy Transfer Assay

Abstract: The interactions of the ligand binding domain (LBD) of androgen receptor (AR) and the AR T877A mutant, found in prostate cancer, with peptides from coactivator and corepressor proteins or random phage display peptides were investigated using in vitro time-resolved fluorescence resonance energy transfer (TR-FRET). Interaction of wild-type AR LBD with the random phage display peptide D11FxxLF was observed with dihydrotestosterone (DHT), testosterone, R1881, estradiol, spironolactone, progesterone, and cortisol r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 64 publications
7
42
0
Order By: Relevance
“…In the presence of OHF the reverse was found for mutant receptors, with interaction only evident between these and the phenylalanine motifs. A similar trend was reported for AR T877A by Ozers et al (2007) who showed, using fluorescence resonance energy transfer, that CPA antagonized its interaction with an FxxLF-containing peptide, while promoting its interaction with an LxxLL-containing peptide.…”
Section: Discussionsupporting
confidence: 83%
“…In the presence of OHF the reverse was found for mutant receptors, with interaction only evident between these and the phenylalanine motifs. A similar trend was reported for AR T877A by Ozers et al (2007) who showed, using fluorescence resonance energy transfer, that CPA antagonized its interaction with an FxxLF-containing peptide, while promoting its interaction with an LxxLL-containing peptide.…”
Section: Discussionsupporting
confidence: 83%
“…For example, LXXLL peptides are shifted in the AR groove toward Lys 720 compared with FXXLF peptides (38 -41). In addition, AR T877A bound to cyproterone acetate (CPA) strongly interacts with LXXLL motifs but less with FXXLF motifs, whereas the opposite is observed if it is bound to hydroxyflutamide (42,43). We therefore determined the interaction capacities of distinct peptides containing FXXLF, FXXFF, FXXMF, and LXXLL sequences with the different AR Leu 701 mutants in the presence of steroids from our panel.…”
Section: Structural Analysis and Modeling Reveal That A Conserved Hydmentioning
confidence: 99%
“…The studies of androgen receptors also revealed the effect of mutations on the agonist/antagonist balance of various ligands (38). The role of coactivator binding affinity as a co-determinant of ligand potency, however, has thus far not been studied in a coherent fashion.…”
Section: Potencies and Efficacies Of Thyroid Hormonesmentioning
confidence: 99%